Synthesis and antimicrobial activity of new ent-kaurene-type diterpenoid derivatives - Marquez-Chacon, Andres Eduardo; Colmenares, Alida Perez; Fermin, Luis Rojas; Aparicio, Rosa; Ramos, Freddy Alejandro; Usubillaga, Alfredo; Obregon, Ysbelia (European Journal of Chemistry, 2023)
This research consists in the synthesis of ent-kaurene-type diterpenoid derivatives from the new natural product ent-kaur-3-acetoxy-15-ene, to carry out structural modifications on the C3 carbon of the ent-kaurene core by introducing different oxygenated groups, especially esters, in order to probe the structure-activity relationship (SAR) against microorganisms. The structure of the compounds was confirmed by FT-IR, 1H NMR, 13C NMR, and GC-MS. The antimicrobial activity of the synthesized derivatives was evaluated, ent-kaur-3-O-(6’,7’-bibenzyl-oxy-caffeoyl)-15-ene (4) exhibited activity against all tested microorganisms: Staphylococcus aureus (16 mm), Enterococcus faecalis (12 mm), Escherichia coli (13 mm), Klebsiella pneumoniae (10 mm), Pseudomonas aeruginosa (8 mm) and Candida krusei (10 mm). These results reveal a remarkable structure-activity relationship over the C3 carbon of the ent-kaurene core, where the presence of oxygenated groups such as hydroxyl or alkyl esters enhances activity.